Laparoscopic Removal of an Ingested Foreign Body with Transesophageal Migration into the Mediastinum - Kapil, Nagaraj (Cureus, 2018)
Removal of a transesophageal migrated foreign body is recommended to prevent injury to adjacent structures. As the endoscopic approach is not feasible for a transesophageal foreign body migrated into the mediastinum, the thoracoscopic approach is recommended. The thoracoscopic approach often requires single lung ventilation and is associated with more pulmonary complications. The use of a laparoscopic approach to remove a mediastinal foreign body has not been reported earlier. In this report, the authors describe a laparoscopic approach for the removal of a transesophageal migrated foreign body into the lower mediastinum.